A review of metal–semiconductor contacts for β-Ga2O3. (23rd September 2022) - Lu, Chao; Ji, Xueqiang; Liu, Zeng; Yan, Xu; Lu, Nianpeng; Li, Peigang; Tang, Weihua
Abstract: β -Gallium oxide ( β -Ga2 O3 ) has been studied extensively in recent decades due to its excellent usability in fabricating a variety of devices, such as solar-blind photodetectors and power devices. However, as an important part of a device, related investigations of β -Ga2 O3 –metal contacts, especially for Schottky contacts, are rare. In this review, we summarize recent research progress on β -Ga2 O3 –metal contacts, including related theories, measurements, fabrication processes, control methods, etc. This review will provide insights for both theoretical understanding of the metal/semiconductor interface, as well as the fabrication process for engineering applications of Ga2 O3 -based devices.